Estudio comparativo entre la aplicación de la técnica tensión-contratensión vs férula oclusal odontológica, en adultos que presentan bruxismo de tipo nocturno - Guevara Ruíz, Ana Cecilia (2018)
The aim of the study is to analyze the efficacy of the tension-contrast (TCT) technique and occlusal splint in trigger points of the masseter muscle in adult patients with nocturnal bruxism. We used two groups of 8 people aged 18 to 50 years, randomly distributed one group for treatment with occlusal splint (“GFO”) and another for treatment with tension-contraction technique (“GE”). The variables applied in both groups were: Pittsburgh Sleep Test; Test of NOT-S or Nordic Orofacial Test-Screening; Algometry and buccal opening. The results indicate that the sleep quality test shows no interaction between groups and significant measurement (F (1,6) equal 1,00, p equal 1,00); in the NOT-S test, there was an interaction between the groups and a significant measurement (F (1,6) equal 15,698, p equal 0,007). In addition, the final comparison for the GE was significant (p equal 0,022) compared to the GFO. The results for algometry in the right masseter muscle indicate interaction between groups and measurement of both groups (F (1,6) equal 15,745, p equal 0,007). It was also observed that the final comparison for the GE was significant (p equal 0,010) compared to the GFO; however, in algometry of the left masseter muscle showed an interaction between group and significant measurement (F (1,6) equal 12,155, p equal 0,01), showing that the final comparison for the GE was significant (p equal 0,000) compared to the GFO The results of the evaluation of the mouth opening indicates significant interaction between group and measurement (F (1,6) equal 20,672, p equal 0,004), additionally it was observed that the final comparison for the EG was significant (p equal 0,000) compared to the GFO It was concluded that the technique of TCT versus the treatment of the occlusal splint shows greater efficacy, and this is reflected in the results obtained in the algometry for the improvement of the pain threshold, especially in the right masseter muscle and also in the mouth opening . The results of the sleep quality test and the NOT-S test showed no significant changes in the patients of both study groups.